Improving the Process of Enteral Nutrition Preparation With Milk Technicians: Perceptions of Cost, Time, and Quality. (April 2016) - Brock, Whitney W.; Cunningham, Craig A.; Brandon, Debra H.; Hoehn, Valerie; Carter, Brigit
Abstract : Background: Neonatal intensive care nurses have historically been responsible for preparing enteral feedings—a costly and time-consuming process that may require leaving the bedside. To address these concerns, the Milk Technician Program was implemented at a major military treatment facility. Milk technicians were specially trained and responsible for handling, storing, and preparing enteral feeds. Purpose: To determine effectiveness of the Milk Technician Program, changes in length of time required to first attain full feeds, cost of feeding preparation, adherence to feeding preparation procedures, and nurse and milk technician role variables were evaluated. Methods: A pre-/postdesign was used to compare length of time to full enteral feedings and cost. A plan-do-study-act design was used to evaluate protocol adherence and to identify and evaluate nurse and milk technician role variables. Data were collected via surveys, direct observations, and retrospective chart reviews to determine the overall effectiveness of this intervention. Results: The average time for extremely and very preterm infants (<28 to 31 weeks) to first reach full feeds decreased from 32 to 19 days, t (33.1) = 2.33, P = .026, d = 0.704. Estimated feeding preparation cost savings for all infants admitted to the unit was 767 per day. Observed milk technician adherence to preparation procedures was 95.5%. Most nurses reported that the program saved time (97%) and all milk technicians reported improved job satisfaction. Nurses expressed concerns about accuracy and safety of preparation. Milk technicians reported concerns with communication, supplies, and lack of perceived support. Implications for Practice: Milk technicians offer significant benefit to infants and nurses in the neonatal intensive care unit, including reducing time for infants to reach full feeds, saving nurses' time, and reducing costs. Implications for Research: Further research is needed to identify ideal educational backgrounds for milk technicians and to directly measure the effect of milk technicians on hospital length of stay and infant growth parameters.